The effectiveness of breakwater shape: Fluid particle behavior simulation. Issue 1 (April 2021) - Muliyati, D; Sumardani, D; Siswoyo, S; Bakri, F; Handoko, E; Permana, H
Abstract: The simulation of physical phenomena between fluid and its boundary is a fascinating study because of its application in various fields of engineering. In this simulation, we analyze how fluids are arranged as granular particles with certain conditions interacting with the wall. The walls are varied as the characters that represent the shape of the breakwater building. This simulation compares the effectiveness of commonly used wave barriers. Wave barriers are used to hold the waves from reaching the land. In this, the simulation used two types of wave holders in the form of tetrapod and cubic, which are placed on a sloping surface. Next, an analysis of the farthest distances from the variations in the speed of the waves and the types of waves holds. Simulation results show that tetrapods are able to withstand wave speeds better than cubic.